Is cloud computing the digital solution to the future of banking? - Cheng, Maoyong; Qu, Yang; Jiang, Chunxia; Zhao, Chenchen (Journal of Financial Stability, 2022)
This study investigates the impact of banks’ strategic move to cloud computing on bank performance and risk-taking. Based on a novel index of banks’ exposure to cloud computing, we find that banks’ adoption of cloud computing is associated with lower cost efficiency, higher profit efficiency, and greater operational risk using data on Chinese banks over the period 2008–2019. We also find that cloud computing interacts with other newly emerging technologies, leading to synergy gains in cost efficiency and operational risk control but with a substitutive effect on profit efficiency from blockchain. The findings are of timely policy importance and practical relevance for regulators, policy-makers, and bank managers.